The development of current treatments for tuberculosis - Nunn, Andrew (Henry Stewart Talks, 2013)
Early trials demonstrated the need for giving more than one drug to avoid the problems of acquired drug resistance, Short course chemotherapy highly effective provided rifampicin given throughout, HIV coinfection has presented new challenges to effective treatment, New methods needed to identify potential regimen candidates for phase III
Archived at 2021/08/31